Working in a world of hurt : trauma and resilience in the narratives of medical personnel in warzones - Acton, Carol, 1958-; Potter, Jane (Lecturer) (Cultural history of modern war., 2016)
'Working in a World of Hurt' uncovers and analyses the range of responses to psychological trauma by male and female medical personnel in wartime in the 20th and early 21st centuries.